The Effectiveness of Using Games Two Truths and a Lie In Increasing Students’ Speaking Ability at SMP Labschool Untad Palu - Fauziah Rismauliani; Aminah Suriaman; Mashuri Mashuri; Abd Kamaruddin (Journal of General Education and Humanities, 2025)
The study aimed to determine the effectiveness of using the "Two Truths and A Lie" game in improving the speaking skills of seventh-grade students at SMP Labschool Untad Palu. This research was motivated by the students' persistent challenges, including low motivation and speaking anxiety, often exacerbated by non-interactive teaching methods. Employing a quasi-experimental design with a pre-test and post-test control group, the study involved a sample of 45 students. Data analysis using SPSS confirmed that the post-test scores of the experimental group followed a normal distribution, justifying the use of parametric tests. The mean scores showed a substantial increase in the experimental group, rising from 9.09 to 15.95, significantly higher than the control group’s increase (from 10.40 to 14.45). This difference was confirmed as statistically significant by the paired sample t-test, supporting the hypothesis. The findings conclusively demonstrate that the "Two Truths and A Lie" game is significantly effective in boosting students' confidence, improving fluency, and developing critical thinking skills, providing empirical insight into the value of incorporating fun and interactive teaching methods.